Immune reconstitution syndrome due to bacillus Calmette-Guérin after initiation of antiretroviral therapy in children with HIV infection - Puthanakit T. (2014)
The immune reconstitution syndrome caused by bacillus Calmette- Guérin (BCG) was found in 4 HIV-infected children who were immunized with BCG at birth. The localized, suppurative, BCG-related complications developed within 10 weeks after initiation of antiretroviral therapy. The incidence rate was 2.7 cases per 100 persons (95% confidence interval, 0.7-6.7). Patients responded well to treatment with isoniazid and rifampicin. © 2005 by the Infectious Diseases Society of America. All rights reserved.